Analysis of Factors Related to Employee Performance at the Aceh Provincial Health Office in 2019 - Teuku Mukhlis; Nizam Ismail; Said Usman; Irwan Saputra; Hajjul Kamil (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Background:. The performance of the Aceh Provincial Health Office is closely related to the attitudes of its employees towards their own work, work situation, cooperation between leaders and fellow employees. Actualized performance by employees is also supported by several factors Objective: analyzing factors related to the performance of Aceh Provincial Health Office employees in 2019 Research Method: This type of research is observational using a cross sectional design. Statistical analysis using multiple regression Results: there is a impact of compensation (X1), leadership style (X2) work discipline (X3) and application of sanctions (X4) with the performance of the Aceh Provincial Health Office Staff and Conclusion: factors that influence performance are compensation, leadership style work discipline and the imposition of sanctions.